Optimalisasi Manajemen Sumber Daya dalam Penggunaan Aplikasi ELSA untuk Peningkatan Keterampilan Speaking dan Pronunciation di SMK Telkom Makassar - Yani, Selviyani; Novia, Lely; Vidia, Rifani; Suli, Virgita Crustia; Muhiddah, Audyna; Chalik, Muh Rezky (Welfare : Jurnal Pengabdian Masyarakat, 2025)
English speaking skills are an important aspect for Vocational High School (SMK) students to be better prepared to face the challenges of the world of work. However, many students experience problems in pronunciation, fluency, and confidence when speaking. This service program aims to improve students' speaking skills by utilizing an artificial intelligence-based application, ELSA Speak. This activity was carried out at SMK Telkom Makassar with participants from the extracurricular English Meeting Club (EMC). Participatory Action Research (PAR) method was applied in this program, which includes needs analysis, planning, training implementation, and evaluation using questionnaires. Results showed that the use of ELSA Speak had a positive impact on students' pronunciation, fluency and confidence. The majority of participants felt significant improvements in speaking, and they were more comfortable and confident in using English. Thus, artificial intelligence technology can be an innovative solution in improving vocational students' speaking skills in an effective, engaging, and easy-to-implement way in the learning process.